Assessing food safety risks in low and middle-income countries - Makita, K.; Haan, Nicoline C. de; Hung Nguyen-Viet; Grace, Delia (Elsevier, 2019)
Foodborne disease burden in low and middle-income countries is high. In these countries, majority of foods are distributed through informal value chains and sold in wet markets. In this chapter, food safety risk analysis frameworks, and application of them into informal value chains are introduced. Informally marketed foods tend to have direct or indirect contamination from unhygienic environment, and importance of ecosystem thinking is described. Moreover, gender aspects of foodborne disease are explained.